Prenatal Diagnosis of Isolated Agnathia-Otocephaly: A Case Report and Review of the Literature - Kazuhiro Kajiwara; Tomohiro Tanemoto; Chie Nagata; Aikou Okamoto (Case Reports in Obstetrics and Gynecology)
Agnathia is a rare disease characterized by the absence of a mandible. Few cases of prenatally diagnosed isolated agnathia have been reported. We present a case report and review of the literature of prenatally diagnosed agnathia. A 38-year-old woman (gravida 0, para 0) was referred to our hospital at 28 weeks and 3 days of gestation for fetal evaluation because of polyhydramnios and suspected facial anomalies. Three-dimensional ultrasonography and MRI indicated agnathia. Premature rupture of the membranes occurred before the parents could reach a decision on the postnatal treatment. We performed emergency cesarean section on the second day of the 33rd week of gestation. The neonate was deemed nonresuscitable and he died of airway obstruction shortly after birth. Because agnathia is associated with very poor prognosis, accurate prenatal diagnosis and detailed counseling should be promptly provided before unexpected delivery to the parents for the determination of postnatal treatment.